2020
DOI: 10.1111/dth.14267
|View full text |Cite
|
Sign up to set email alerts
|

Micro needling: A novel therapeutic approach for androgenetic alopecia, A Review of Literature

Abstract: Androgenetic alopecia (AGA) is an androgen-dependent hereditary trait resulting in hair miniaturization. It is the most common type of alopecia in men and women. During the last years, multiple treatment modalities have been studied, but only topical minoxidil and finasteride have been approved by the US Food and Drug Administration. Microneedling (MN) is a minimally invasive technique that induces collagen formation, as well as growth factors production and neovascularization. Even though not many studies of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Interestingly, some studies reported significant increases in hair density even for the placebo treatment (e.g., from 151.04 ± 41.99 to 166.72 ± 37.13 hairs/cm 2 , mean ± SD [ 43 ]). Although the authors explained such effects as resulting from a possible diffusion of the growth factors from the PRP-injected to the placebo-injected area, it is also plausible that microstimulation by needle puncture itself exerts beneficial effects on hair growth; this principle is currently applied in microneedling, another novel therapy used for AGA [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, some studies reported significant increases in hair density even for the placebo treatment (e.g., from 151.04 ± 41.99 to 166.72 ± 37.13 hairs/cm 2 , mean ± SD [ 43 ]). Although the authors explained such effects as resulting from a possible diffusion of the growth factors from the PRP-injected to the placebo-injected area, it is also plausible that microstimulation by needle puncture itself exerts beneficial effects on hair growth; this principle is currently applied in microneedling, another novel therapy used for AGA [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“… 10 Additionally, multiple studies have reported that as a safe and effective adjunctive therapy for androgenetic alopecia, microneedling treatment performs beneficial effects on promoting hair growth and enhancing the penetration of local therapies. 11 , 12 Therefore, this study aims to evaluate the efficacy and safety of a combined treatment for moderate and severe AGA incorporating electric microneedle techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Significant improvements were noted in the combined treatments group per investigator's and subjects' ratings, as well as hair counts 117 . Similar studies were also conducted and yielded equivalent results of increased hair density and thickness 118–121 . Dhurat and Parajuli reported a case series of patients who were poor responders to conventional therapies and gained significant improvement after the addition of microneedling 122,123 …”
Section: Adjuvant Therapymentioning
confidence: 76%
“… 117 Similar studies were also conducted and yielded equivalent results of increased hair density and thickness. 118 , 119 , 120 , 121 Dhurat and Parajuli reported a case series of patients who were poor responders to conventional therapies and gained significant improvement after the addition of microneedling. 122 , 123 Jha et al also reported superior clinical outcomes seen in the PRP, microneedling, and topical minoxidil patients vs. monotherapy patients.…”
Section: Adjuvant Therapymentioning
confidence: 99%